Effect of weed control methods and fertilizer levels on growth characters of Populus deltoides Bartr. nursery - Kumari, Sushil; Bhardwaj, K.K.; Khajuria, Sanjay; Dhillon, R.S.; Bangrawa, K.S. (Indian Journal of Agroforestry, 2020)
Selection of suitable weed control method and application of optimum fertilizer dose play an important role for raising healthy poplar plants and getting higher income from the nursery. The study conducted in the nursery showed significant effect of different weed control methods and fertilizer levels on the growth parameters viz. fresh and dry weight of shoot and root per plant, total biomass per plant. Application of inorganic (200 kg N + 50 kg P2 O5 /ha) and organic fertilizers (farmyard manure @ 20 t/ha) produced significantly higher fresh and dry weight of shoot and root and total biomass as compared with other treatments. Weeds were effectively controlled by manual weeding at 30 days interval whereas application of herbicide was found effective on the all growth parameters of poplar plants as compared with control treatments.